Optimalisasi Penggunaan Tax Center dalam Meningkatkan Pelayanan Pajak bagi Pihak Internal dan Eksternal Politeknik Negeri Bengkalis - Novira Sartika; Nurhazana Nurhazana; Husni Mubarak (P3M Politeknik Negeri Bengkalis, 2025)
The purpose of this community service activity is to optimize the role of the Politeknik Negeri Bengkalis tax center in improving services to the community, especially taxpayers, both internal and external to the Bengkalis State Polytechnic, such as providing tax education to the community, especially taxpayers, explaining how to use the core tax application, and providing transparent and accountable information regarding current tax management thru an electronic information board. By utilizing the electronic information board, the Politeknik Negeri Bengkalis tax center can display current tax management information, upcoming Politeknik Negeri Bengkalis tax center activities, past Politeknik Negeri Bengkalis tax center activities, and other announcements more easily and quickly. It is hoped that the results will increase the community's knowledge and understanding of taxes, update information regarding current tax management, and inform the community about the activities managed by the Politeknik Negeri Bengkalis tax center, thereby increasing public trust in the government as tax manager.